RETRACTED ARTICLE: MiRNA-211 suppresses cell proliferation, migration and invasion by targeting SPARC in human hepatocellular carcinoma - Biao Deng; Lei Qu; Jinfang Li; Jiaqing Fang; Shouwen Yang; Zhongwei Cao; Zhechuan Mei; Xing Sun (Scientific Reports, 2016)
Abstract Previous studies have shown that the expression of miR-211 was downregulated in hepatocellular carcinoma (HCC). However, the molecular function and mechanism of miR-211 in HCC growth and invasion are largely unclear. We found that miR-211 is downregulated in HCC tissues and cell lines, respectively. Further results showed that low miR-211 associated with TNM stage, vein invasion status and poor prognosis. Ectopic expression of miR-211 effectively suppressed HCC cell proliferation, migration and invasion both in vitro and in vivo. We identified SPARC as a bona fide target of miR-211 and overexpression of miR-211 decreased the mRNA and protein expression of SPARC. Finally, we confirmed that the overexpression of SPARC in miR-211-expressing HCC cells can partially restore the inhibitory effect of miR-211. Taken together, our results demonstrated that loss of miR-211 expression and thus uncontrolled SPARC overexpression might drive progression of HCC, which may provide a novel therapeutic strategy for the treatment of HCC.